Correction coefficients of distortion and vibration period for buildings due to soil-structure interaction - Ticona, A. M. (2020)
The present research analyzed the influence of the soil structure interaction (SSI) in buildings, varying geotechnical parameters and height, considering 3 international codes. The responses obtained from the structures taking into account the SSI, were compared with the responses of fixed-base buildings, being the main control variables: the period and the drift. It was determined that the estimated range in which the period of the structure increases is from 30 to 98%, demonstrating the influence of considering soil flexibility. Due to the variability of the responses obtained, an adjustment factor is proposed to predict said amplification of the control variables, depending on the height of the building and the ground.